Malformations of the Cerebral Commissures - Lena, Germana; La Cognata, Daria; Zanghì, Antonio; Vecchio, Michele; Chiaramonte, Rita; Falsaperla, Raffaele; Marino, Francesco; Palmucci, Stefano; Belfiore, Giuseppe; Basile, Antonio; Praticò, Andrea D. (Journal of Pediatric Neurology, 2024)
Malformations of the cerebral commissures are abnormalities involving the structures which connect the brain hemispheres. The main cerebral commissures are the anterior commissure, the hippocampal commissure, and the corpus callosum, which is the largest and best known of the three and connects the neocortex of the two cerebral hemispheres. Commissures of more reduced extension are the posterior commissure and the habenular commissure. They derive embryologically from the same structure, the commensurate plate. Any interference in the embryological development of the brain commissures may cause an anomaly of all the three commissures or of a single commissure, as well as any combination of anomalies of each of them.Each of these three commissural traits may be absent, isolated, or in combination. The abnormality of the commissures, in addition, can be complete or partial, with dysplasia of the meninges, with multicystic dysplasia of the interhemispheric meninges, in the context of Aicardi syndrome or with the presence of interhemispheric lipomas.The complete agenesis of the commissures (“classic” form) is the most common form and encompasses more than a third of the cases. In complete agenesis, by definition, both the corpus callosum and the hippocampal commissure are totally absent.Anomalies of the commissural structures associated with dysplasia of the meninges include the agenesis of the corpus callosum with interhemispheric cysts (a complex spectrum of clinical and neuroradiological conditions characterized by the associated presence of an interhemispheric cyst formed by communicating cavities) and the agenesis of commissures with interhemispheric lipomas that are usually located in the subarachnoid space.Genes responsible for axonal migration to the commissural plate and those responsible for crossing and connections with the neurons of the contralateral hemisphere are multiple, so that malformations of the cerebral commissure/corpus callosum can be found in numerous malformative syndromes with other multiple associated abnormalities.
Keywords: cerebral commissures; corpus callosum; genetics; child neurology